Reforming mathematics education in Indonesia using the productive pedagogies framework - Suhendra (Curtin University, 2015)
The overarching aim of the study was to examine, on a small scale, the usefulness of the Productive Pedagogies framework to reform the current practices of teachers in Indonesia. The findings indicated that, by implementing the framework, the teachers improved the interactions among students, made mathematics more relevant to students’ lives and enhanced social justice in mathematics classrooms. As a result, the students became more enthusiastic to attend and more engaged in their mathematics classes.